Inserção e sobre-escolaridade dos jovens no mercado de trabalho diante das transformações econômicas e sociais brasileiras na última década - Felipe da Silva Basso (2017)
This work aims to evaluate the insertion and the overeducation of young people in the labor market of brazilian metropolitan regions. Particularly, it is intended to analyze not only if the young person is working or not, but also the type of occupation in which they are inserted (formal or informal, public or private) and also the quality of the insertion (adequately educated or overeducated). Therefore, it purposes to establish the determinants of insertion, the impact of educational expansion and economic cycles, differences between genders and mainly compare young people according to their educational status (non-graduated, recent graduated and graduated for longer). For attending the goals, four models were estimated, for the first one it is aplied the logit method in which the dependent variable is binary and for the other ones it is aplied the multinomial logit in which the dependent variable has more than two alternatives, each one of them has three versions: with all young people, only with men and only with women. The results indicates that the greater the age, the greater the probability of working and that the young people who still live with their parents are less likely to work. In addition, it was found that in years of economic growth the probability of working increased and in years of recession or stagnation this probability decreased, there was a trend of formalization in the labor market throughout the period and jobs in the public sector are less volatile in relation to the economic variations. The degree of overeducation is high among young people with college degree, more than a half of the employed ones works overeducated, which represents an inefficiency in the allocation of these people in the labor market. However, there has not been a significant increase over the last years in the overeducation rate and it means that the supply and demand for more schooling labor force have moved in the same direction. With respect to gender differences, women are less likely to work and this probability may be even lower depending on family arrangements, it is a fact that many women have to give up of their professional career because of domestic activities and for their children's education. Finally, young people with college degree improve substantially the chances of working and this probability is even greater after a time of being graduated, by the way, a time after being graduated also increases the chances of working in occupations where the level of education required by the position is the same level education acquired by the the individual.